Teknik Empty Chair : Membangun Komunikasi Intrapersonal dan Ruang Aman bagi Ekspresi Diri Remaja - Giska Khoerunisa; Risma Rahmawati; Inna Sofwatillah; Imalatul Khairat (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Adolescence is a complex developmental stage marked by identity exploration and intense emotional changes. Teenagers often struggle to express their feelings openly, both to others and to themselves. This difficulty is exacerbated by cultural factors, lack of emotional education, and the stigma surrounding mental health, which prevent adolescents from finding a safe space to express themselves. This study aims to explore the effectiveness of the empty chair technique in building intrapersonal communication and creating a safe space for adolescent self-expression. The research method used is qualitative descriptive through a literature review. The results show that the empty chair technique from Gestalt therapy is effective in helping adolescents express inner conflicts, increase self-awareness, emotional regulation, and self-esteem, particularly among victims of bullying. This technique allows adolescents to engage in symbolic dialogue with parts of themselves in a reflective and therapeutic manner. The implications of this research suggest that the empty chair technique can be a strategic approach in school and community counseling to support the holistic psychosocial development of adolescents.